Evaluation of Therapeutic Antibiotics After Laparoscopic Cholecystectomy: A Quasi- Experimental Study - Mayun, Komang Abdi Baskara; Sudartana, Ketut; Sudarsa, Wayan; Sueta, Made Agus Dwianthara; Sudiasa, Ketut; Budiarta, Ida Bagus (Universitas Wijaya Kusuma Surabaya, 2025)
Background: The routine use of postoperative therapeutic antibiotics after laparoscopic cholecystectomy remains controversial due to limited evidence of clinical benefit and concerns over antimicrobial resistance. Objective: To evaluate the effect of postoperative therapeutic antibiotics on surgical site infections (SSI) and laboratory outcomes after laparoscopic cholecystectomy. Methods: A quasi-experimental, post-testonly study with a non-equivalent control group was conducted at RSUP Prof. Dr. I.G.N.G. Ngoerah (September 2023–March 2024). Fifty-six patients were divided into two groups: postoperative antibiotics (cefoperazone followed by cefixime) versus no antibiotics. SSI was assessed on postoperative days 7 and 30 using the ASEPSIS scoring system. Laboratory parameters (leukocytes, neutrophils, lymphocytes, hemoglobin, and platelet counts) were compared between groups. No SSI occurred in either group. Laboratory outcomes showed nostatistically significant differences between the antibiotic and non-antibiotic groups (p > 0.05). Results: The mean age of participants was 45.2 ± 15.1 years, with female predominance. Conclusion: Postoperative therapeutic antibiotics did not reduce SSI rates or alter laboratory outcomes followinglaparoscopic cholecystectomy. Routine use is not supported in mild to moderate cases, and limiting unnecessary antibiotics may help reduce antimicrobial resistance.